2022
DOI: 10.3389/fnins.2022.889211
|View full text |Cite
|
Sign up to set email alerts
|

A Prebiotic Diet Alters the Fecal Microbiome and Improves Sleep in Response to Sleep Disruption in Rats

Abstract: Sleep disruption is a challenging and exceedingly common physiological state that contributes to a wide range of biochemical and molecular perturbations and has been linked to numerous adverse health outcomes. Modern society exerts significant pressure on the sleep/wake cycle via myriad factors, including exposure to electric light, psychological stressors, technological interconnection, jet travel, shift work, and widespread use of sleep-affecting compounds. Interestingly, recent research has identified a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…Both in vitro and in vivo studies have revealed that P. distasonis displays anti-inflammatory effects and the ability to restore the epithelial barrier in a cell culture model and strengthen the intestinal barrier to attenuate intestinal inflammation in a mouse model of colitis 43 . A prebiotic diet increases the relative abundance of P. distasonis , improves sleep during repeated sleep interruptions and sleep resumption 44 , alters the fecal bile acid profile, and promotes the recovery and readjustment of sleep and circadian rhythms after circadian rhythm interruptions 45 . However, P. distasonis could induce depressive-like behavior by synthesizing neurotransmitters in a mouse with Crohn’s disease 46 and exacerbate the symptoms of amyotrophic lateral sclerosis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have revealed that P. distasonis displays anti-inflammatory effects and the ability to restore the epithelial barrier in a cell culture model and strengthen the intestinal barrier to attenuate intestinal inflammation in a mouse model of colitis 43 . A prebiotic diet increases the relative abundance of P. distasonis , improves sleep during repeated sleep interruptions and sleep resumption 44 , alters the fecal bile acid profile, and promotes the recovery and readjustment of sleep and circadian rhythms after circadian rhythm interruptions 45 . However, P. distasonis could induce depressive-like behavior by synthesizing neurotransmitters in a mouse with Crohn’s disease 46 and exacerbate the symptoms of amyotrophic lateral sclerosis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ergothioneine, a metabolite of Lactobacillus reuteri, increased REM sleep duration in rats [127]. A prebiotic diet has prolonged both REM and nREM sleep in another study in rats [128]. A recent review on this topic concluded that these alterations could lead to improvement in mental disorders in patients with sleep disorders [129].…”
Section: Oral Supplementations In Sleep Disordersmentioning
confidence: 99%
“…Fascinatingly, prebiotics may even influence sleep quality; the prebiotic GOS and polydextrose (PDX) could alleviate stress‐induced sleep disturbances in rats. The GOS/PDX prebiotic diet increased the relative abundance of Parabacteroides distasonis and altered the fecal bile acid pool, and these changes were associated with improved sleep patterns in stressed rats, indicating a potential role for prebiotics in treating stress‐related sleep disorders 166 . In the field of metabolic diseases, prebiotic xylooligosaccharides (XOS) could mitigate high‐fat diet (HFD)‐induced metabolic syndrome in rats by increasing the number of Bifidobacteria and Lactobacilli and reducing the abundance of Proteobacteria 167 .…”
Section: Effectiveness and Mechanisms Of Prebiotics In Treating Diseasesmentioning
confidence: 99%
“…The GOS/PDX prebiotic diet increased the relative abundance of Parabacteroides distasonis and altered the fecal bile acid pool, and these changes were associated with improved sleep patterns in stressed rats, indicating a potential role for prebiotics in treating stress‐related sleep disorders. 166 In the field of metabolic diseases, prebiotic xylooligosaccharides (XOS) could mitigate high‐fat diet (HFD)‐induced metabolic syndrome in rats by increasing the number of Bifidobacteria and Lactobacilli and reducing the abundance of Proteobacteria . 167 Nonalcoholic fatty liver disease (NAFLD) is the most common metabolic disease worldwide, and it may also reduce the insulin resistance in NAFLD patients through a chain reaction to induce hyperinsulinemia and increase the risk of bladder cancer.…”
Section: Effectiveness and Mechanisms Of Prebiotics In Treating Diseasesmentioning
confidence: 99%